The relationship knowledge of occupational health and safety (K3) and attitudes towards awareness behavior in vocational high schools - Sirulladuni, Ahmad; Hadi, Samsul; Johan, Arif Bintoro; Hashim, Azhari Md (Universitas Sarjanawiyata Tamansiswa, 2024)
The Relationship of K3 Knowledge and Attitude with K3 Behavioral Awareness in the Machining Workshop of SMK Muhammadiyah Prambanan for the 2022/2023 Academic Year. This study aims to determine 1) The relationship of K3 knowledge with awareness of K3 behavior; 2) The relationship of attitude with K3 behavioral awareness; 3) The relationship of K3 knowledge and attitudes together with K3 behavioral awareness. This study used the expost facto method. Data collection using questionnaires with a population of grade X students totaling 30 respondents. The descriptive and regression. The results showed that: 1) There is a positive relationship between K3 knowledge and attitudes together towards K3 behavioral awareness with a coefficient of determination (R Square) of 0.314 which means that the K3 knowledge variable has a contribution to K3 behavior awareness of 31.4%; 2) there is a positive relationship of attitude towards K3 behavioral awareness with the coefficient of determination (R Square) of the attitude variable of 0.481 which means that the attitude variable has a contribution to K3 behavioral awareness of 48.1%; 3) the variables between K3 knowledge and attitude together affect K3 behavioral awareness with a coefficient of determination (R Square) of K3 knowledge and attitude of 0.638 which means that K3 knowledge variables have a contribution to K3 behavior awareness of 63.8%.